Reforming the French health-care system: the quest for accountability. (September 2018) - Simonet, Daniel
The resurgence of New Right politics in the late 1970s and 1980s (e.g. 'Reaganomics' and 'Thatcherism'), which were pro-market and pro-private sector (Lorenz, 2012 ), has increased the reliance on the private sector for the provision of public services. In France, the support for the private sector is no longer a partisan or ideological issue, but rather a pragmatic and increasingly routine approach to the delivery of public services. Whether this will improve the efficiency of the health-care system is still open to question. The article: investigates the use of the New Public Management toolbox (Goldfinch and Wallis, 2009 : 151) in the French health-care system; examines its selective adoption; and assesses its impact on the accountability and transparency of the medical profession. The French government eventually opted for a re-centralization of the health-care system for monitoring purposes. The reforms antagonized the medical profession and strengthened private care providers. Point for practitioners: Despite reiterated calls for devolution, the implementation of New Public Management in the French health-care system led to a greater re-centralization and rising regulations for efficiency purposes. It also allowed the French administrative elite to regain its prerogatives and regional health agencies to reform more rapidly than a multitude of local public organizations. The quest for greater accountability remains an ongoing process.